Preparation and use method of lanthanum-iron functionalized silicon dioxide aerogel phosphorus removal agent

By introducing lanthanum and iron into the silica aerogel prepared by water glass, combined with the packaging technology of cellulose acetate, a functionalized silica aerogel phosphorus removal agent was prepared, which solved the negative impact of existing phosphorus removal agents on water bodies and the increase in sludge, and achieved the reusable use of phosphorus removal agents and the effect of no secondary pollution to water.

CN119897080APending Publication Date: 2025-04-29GUANGDONG PAPER IND RES INST
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510268523.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-03-07
Publication Date
2025-04-29

AI Technical Summary

Technical Problem

Existing phosphorus removal adsorbents such as iron salt systems and aluminum salt systems will have a negative impact on the water during use, and the lanthanum functionalized aerogel will increase the amount of sludge when used directly, making it difficult to achieve the effect of reusable and no secondary pollution to water.

Method used

By introducing lanthanum and iron into the silica aerogel prepared by water glass, a lanthanum iron functionalized silica aerogel phosphorus removal agent was prepared, and cellulose acetate was used as the encapsulator to prepare phosphorus removal materials by hot pressing, etc., so as to achieve desorption and reuse of the material after phosphorus removal.

Benefits of technology

It realizes the reusable use of phosphorus removal agents, no secondary pollution to water, simple operation, safe and environmentally friendly, low cost, and has the advantages of industrial promotion.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention relates to the technical field of adsorption materials, in particular to preparation and use methods of a lanthanum and iron functionalized silica aerogel phosphorus removal agent. Sodium silicate serves as a silicon source to prepare silica aerogel, lanthanum and iron functional modification is conducted on the silica aerogel under the high-temperature condition, then cellulose acetate serves as a carrier to prepare an adsorption material, and the lanthanum and iron functionalized silica aerogel phosphorus removal agent is prepared. The water glass can be reused after being subjected to desorption treatment in adsorption equilibrium, the water glass synthesis raw materials are wide in distribution and low in cost and have the advantage of industrial popularization, and the cellulose acetate is a derivative of cellulose, has the advantages of biodegradability, reproducibility and good thermal plasticity and can be used for preparing adsorption materials of any shape and size. The phosphorus removal agent provided by the invention has the advantages of safety, environmental protection, reusability, no secondary pollution to water, high phosphorus removal efficiency of 80% or more and the like, the phosphorus removal efficiency reaches 70% or more after two times of desorption treatment, and the phosphorus removal agent has a wide application prospect.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of adsorption materials, and in particular to a preparation method of a lanthanum-iron functionalized silica aerogel dephosphorization agent and a use method thereof. Background Art

[0002] To solve the problem of eutrophication of water bodies caused by phosphorus pollution, the main methods of water phosphorus removal include chemical precipitation, biological method and adsorption method. Chemical precipitation method of phosphorus removal is easy to operate and has a quick effect, but it uses a large amount of chemical reagents and has high operating costs; biological method has low operating costs, but has relatively high requirements for operating conditions and environment, and poor stability; adsorption method uses electrostatic effects, complexation and reverse surface adsorption to adsorb phosphorus and other substances in sewage on the surface of the material. It has the advantages of simple process, easy operation, good stability and large adsorption capacity. The phosphorus removal adsorbents currently used are mainly iron salts and aluminum salts, among which the Al produced by aluminum salts 3+ It will have an adverse impact on the ecological environment. The Fe in iron salts 3+ It will cause negative impacts such as darkening of water color and lowering of pH.

[0003] Lanthanum has a strong adsorption capacity for phosphates, and its effect is better than the currently used iron salt and aluminum salt dephosphorizers. Silica aerogel has rich porosity and specific surface area, which provides a guarantee for the adsorption and functional modification of phosphorus in sewage. However, the direct use of lanthanum functionalized aerogel will increase the amount of sludge in sewage.

[0004] Therefore, according to the above-mentioned related technologies, it is urgent to develop a preparation method and use method of a lanthanum iron functionalized silica aerogel dephosphorization agent. Summary of the invention

[0005] In view of this, the purpose of the present invention is to propose a preparation method of a lanthanum iron functionalized silica aerogel dephosphorus remover and a method of using the same, so as to provide a dephosphorus remover that is reusable and has no secondary pollution to water.

[0006] Based on the above purpose, the present invention provides a preparation method and use method of a lanthanum-iron functionalized silica aerogel dephosphorization agent.

[0007] A method for preparing a lanthanum-iron functionalized silica aerogel dephosphorization agent comprises the following steps:

[0008] Step S1. Add water glass to deionized water and stir for 30 minutes to dilute, then add dilute sulfuric acid at a speed of 1200-2000 rpm, and then age at room temperature for 12-24 hours after the dripping is completed for 3 hours to obtain gel sample 1;

[0009] Step S2. Gel sample 1 was crushed, washed with water for 5 times, filtered to remove impurities, and then soaked with anhydrous ethanol and n-hexane to replace the solvent in the gel, and then soaked with trimethylchlorosilane for 3 hours to obtain sample 2;

[0010] Step S3. Drying sample 2 at a constant temperature of 60-90° C. to obtain silica aerogel, and grinding the aerogel in a ball mill for 2-3 h to obtain powder sample 3;

[0011] Step S4. dissolving lanthanum nitrate hexahydrate and ferric chloride in anhydrous ethanol and mixing them evenly to obtain a lanthanum-iron composite solution;

[0012] Step S5. Add the powder sample 3 to the lanthanum-iron composite solution, stir at 50°C for 4 hours to remove ethanol, and then calcine in a muffle furnace at 600-700°C for 4 hours to obtain a silica aerogel adsorbent introduced with iron and lanthanum elements, wash the silica aerogel with ethanol, and dry at 80-85°C to obtain sample 4;

[0013] Step S6. Dissolve cellulose acetate in acetone, stir for 30 minutes at room temperature, add sample 4 and water, stir evenly, pour the mixture into a mold, remove the solvent, and obtain a lanthanum-iron functionalized silica aerogel dephosphorus agent.

[0014] Preferably, the usage ratio of water glass, deionized water and dilute sulfuric acid in step S1 is 30:120-150:20-30.

[0015] Preferably, the solid content of the water glass in step S1 is 36%.

[0016] Preferably, the solid content of the diluted water glass in step S1 is 6%-7.2%.

[0017] Preferably, the concentration of the dilute sulfuric acid in step S1 is 15%-20%.

[0018] Preferably, the usage ratio of the sample 1, anhydrous ethanol, n-hexane and trimethylchlorosilane in step S2 is 10 g: 150-200 mL: 100-120 mL: 100-120 mL.

[0019] Preferably, the usage ratio of lanthanum nitrate hexahydrate, ferric chloride and anhydrous ethanol in step S4 is 0.01-0.05 g: 0.01-0.025 g: 100 mL.

[0020] Preferably, the usage ratio of cellulose acetate, acetone, sample 4 and water in step S6 is 3-5:45-47:4-8:10-15.

[0021] A method for using a lanthanum iron functionalized silica aerogel dephosphorization agent comprises the following steps: adding the prepared lanthanum iron functionalized silica aerogel dephosphorization agent into phosphorus-containing wastewater, stirring and allowing the agent to settle to remove phosphorus from the phosphorus-containing wastewater.

[0022] Beneficial effects of the present invention:

[0023] The invention provides a preparation method of a lanthanum-iron functionalized silica aerogel dephosphorization agent and a use method thereof. By introducing lanthanum and iron elements into silica aerogel prepared from water glass, simple operation, safety, environmental protection, low cost, wide source and efficient removal of phosphorus in wastewater are achieved. After dephosphorization, the material can be desorbed to achieve the reuse of the dephosphorization material. In addition, cellulose acetate is thermoplastic, biodegradable and renewable. Dephosphorization materials of any shape and size can be prepared by hot pressing and the like. Compared with other silica aerogel materials, the raw materials for preparing water glass are quartz sand and sodium carbonate, which are widely distributed, low cost and have long-term chemical stability and storage stability. The silica aerogel has rich porosity and specific surface area, provides a larger contact area for the introduction of lanthanum and iron elements and the adsorption of phosphorus elements, and has the advantage of industrial promotion. DETAILED DESCRIPTION

[0024] In order to make the objectives, technical solutions and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with specific embodiments.

[0025] Example 1: A method for preparing a lanthanum iron functionalized silica aerogel dephosphorization agent, comprising the following steps:

[0026] S1. Take 30g of water glass with a solid content of 36%, add 120g of deionized water and stir for 30min to dilute to a solid content of 7.2%, then prepare 30g of dilute sulfuric acid with a concentration of 15%, and drip 20g of dilute sulfuric acid at a speed of 1500rpm for 3h, and age at room temperature for 24h to obtain gel sample 1;

[0027] S2. Gel sample 1 was crushed, washed with water 5 times, filtered to remove impurities, and then soaked with anhydrous ethanol and n-hexane to replace the solvent in the gel, and then soaked with trimethylchlorosilane for 3h to obtain sample 2;

[0028] S3. Sample 2 was dried at 85°C to obtain silica aerogel, and ground in a ball mill for 2 h to obtain powder sample 3;

[0029] S4. The powder sample 3 was added to 100 mL of anhydrous ethanol dissolved with 0.05 g of lanthanum nitrate hexahydrate and 0.025 g of ferric chloride, stirred at 50 ° C for 4 h, and then dried in an oven at 85 ° C for 4 h. After removing the ethanol, it was calcined in a muffle furnace at 700 ° C for 4 h to obtain a silica aerogel adsorbent introduced with iron and lanthanum elements. The silica aerogel was washed with ethanol and dried at 80 ° C to obtain sample 4;

[0030] S5. Dissolve 3 g of cellulose acetate in 47 g of acetone, stir at room temperature for 30 min, add 7 g of sample 4 and 12 g of water, stir evenly, pour the mixture into a mold, remove the solvent to obtain a lanthanum-iron functionalized silica aerogel dephosphorus agent.

[0031] Example 2: A method for preparing a lanthanum iron functionalized silica aerogel dephosphorization agent, comprising the following steps:

[0032] S1. Take 30g of water glass with a solid content of 36%, add 150g of deionized water and stir for 30min to dilute to a solid content of 6%, then prepare 20g of dilute sulfuric acid with a concentration of 20%, drip 20g of dilute sulfuric acid at a speed of 1200rpm, drip it for 3h, age at room temperature for 24h, and obtain gel sample 1;

[0033] S2. Gel sample 1 was crushed, washed with water 5 times, filtered to remove impurities, and then soaked with anhydrous ethanol and n-hexane to replace the solvent in the gel, and then soaked with trimethylchlorosilane for 3h to obtain sample 2;

[0034] S3. Sample 2 was dried at 80°C to obtain silica aerogel, and ground in a ball mill for 2 h to obtain powder sample 3;

[0035] S4. The powder sample 3 was added to 100 mL of anhydrous ethanol dissolved with 0.05 g of lanthanum nitrate hexahydrate and 0.015 g of ferric chloride, stirred at 50 ° C for 4 h, and then dried in an oven at 85 ° C for 4 h. After removing the ethanol, it was calcined in a muffle furnace at 600 ° C for 4 h to obtain a silica aerogel adsorbent introduced with iron and lanthanum elements. The silica aerogel was washed with ethanol and dried at 80 ° C to obtain sample 4;

[0036] S5. Dissolve 3 g of cellulose acetate in 47 g of acetone, stir at room temperature for 30 min, add 4 g of sample 4 and 10 g of water, stir evenly, pour the mixture into a mold, remove the solvent to obtain a lanthanum-iron functionalized silica aerogel dephosphorus agent.

[0037] Example 3: A method for preparing a lanthanum iron functionalized silica aerogel dephosphorization agent, comprising the following steps:

[0038] S1. Take 30g of water glass with a solid content of 36%, add 120g of deionized water and stir for 30min to dilute to a solid content of 7.2%, then prepare 30g of dilute sulfuric acid with a concentration of 15%, and drip 20g of dilute sulfuric acid at a speed of 2000rpm for 3h, and age at room temperature for 12h to obtain gel sample 1;

[0039] S2. Gel sample 1 was crushed, washed with water 5 times, filtered to remove impurities, and then soaked with anhydrous ethanol and n-hexane to replace the solvent in the gel, and then soaked with trimethylchlorosilane for 3h to obtain sample 2;

[0040] S3. Sample 2 was dried at 85°C to obtain silica aerogel, and ground in a ball mill for 3 h to obtain powder sample 3;

[0041] S4. The powder sample 3 was added to 100 mL of anhydrous ethanol dissolved with 0.02 g of lanthanum nitrate hexahydrate and 0.01 g of ferric chloride, stirred at 50 ° C for 4 h, and then dried in an oven at 85 ° C for 4 h. After removing the ethanol, it was calcined in a muffle furnace at 700 ° C for 4 h to obtain a silica aerogel adsorbent introduced with iron and lanthanum elements. The silica aerogel was washed with ethanol and dried at 80 ° C to obtain sample 4;

[0042] S5. Dissolve 5 g of cellulose acetate in 45 g of acetone, stir at room temperature for 30 min, add 6 g of sample 4 and 15 g of water, stir evenly, pour the mixture into a mold, remove the solvent to obtain a lanthanum-iron functionalized silica aerogel dephosphorus agent.

[0043] Example 4: A method for preparing a lanthanum iron functionalized silica aerogel dephosphorization agent, comprising the following steps:

[0044] S1. Take 30g of water glass with a solid content of 36%, add 120g of deionized water and stir for 30min to dilute to a solid content of 7.2%, then prepare 30g of dilute sulfuric acid with a concentration of 15%, and drip 30g of dilute sulfuric acid at a speed of 1200rpm for 3h, and age at room temperature for 18h to obtain gel sample 1;

[0045] S2. Gel sample 1 was crushed, washed with water 5 times, filtered to remove impurities, and then soaked with anhydrous ethanol and n-hexane to replace the solvent in the gel, and then soaked with trimethylchlorosilane for 3h to obtain sample 2;

[0046] S3. Sample 2 was dried at 60°C to obtain silica aerogel, and ground in a ball mill for 2 h to obtain powder sample 3;

[0047] S4. The powder sample 3 was added to 100 mL of anhydrous ethanol dissolved with 0.02 g of lanthanum nitrate hexahydrate and 0.015 g of ferric chloride, stirred at 50 ° C for 4 h, and then dried in an oven at 85 ° C for 4 h. After removing the ethanol, it was calcined in a muffle furnace at 600 ° C for 4 h to obtain a silica aerogel adsorbent introduced with iron and lanthanum elements. The silica aerogel was washed with ethanol and dried at 80 ° C to obtain sample 4;

[0048] S5. Dissolve 5 g of cellulose acetate in 45 g of acetone, stir at room temperature for 30 min, add 8 g of sample 4 and 10 g of water, stir evenly, pour the mixture into a mold, remove the solvent to obtain a lanthanum-iron functionalized silica aerogel dephosphorus agent.

[0049] Example 5: A method for preparing a lanthanum iron functionalized silica aerogel dephosphorization agent, comprising the following steps:

[0050] S1. Take 30g of water glass with a solid content of 36%, add 120g of deionized water and stir for 30min to dilute to a solid content of 7.2%, then prepare 30g of dilute sulfuric acid with a concentration of 15%, and drip 30g of dilute sulfuric acid at a speed of 2000rpm for 3h, and age at room temperature for 12h to obtain gel sample 1;

[0051] S2. Gel sample 1 was crushed, washed with water 5 times, filtered to remove impurities, and then soaked with anhydrous ethanol and n-hexane to replace the solvent in the gel, and then soaked with trimethylchlorosilane for 3h to obtain sample 2;

[0052] S3. Sample 2 was dried at 90°C to obtain silica aerogel, and ground in a ball mill for 2 h to obtain powder sample 3;

[0053] S4. The powder sample 3 was added to 100 mL of anhydrous ethanol dissolved with 0.01 g of lanthanum nitrate hexahydrate and 0.02 g of ferric chloride, stirred at 50 ° C for 4 h, and then dried in an oven at 85 ° C for 4 h. After removing the ethanol, it was calcined in a muffle furnace at 700 ° C for 4 h to obtain a silica aerogel adsorbent introduced with iron and lanthanum elements. The silica aerogel was washed with ethanol and dried at 80 ° C to obtain sample 4;

[0054] S5. Dissolve 5 g of cellulose acetate in 45 g of acetone, stir at room temperature for 30 min, add 5 g of sample 4 and 10 g of water, stir evenly, pour the mixture into a mold, remove the solvent to obtain a lanthanum-iron functionalized silica aerogel dephosphorus agent.

[0055] Example 6: A method for preparing a lanthanum iron functionalized silica aerogel dephosphorization agent, comprising the following steps:

[0056] S1. Take 30g of water glass with a solid content of 36%, add 120g of deionized water and stir for 30min to dilute to a solid content of 7.2%, then prepare 30g of dilute sulfuric acid with a concentration of 15%, and drip 20g of dilute sulfuric acid at a speed of 2000rpm for 3h, and age at room temperature for 12h to obtain gel sample 1;

[0057] S2. Gel sample 1 was crushed, washed with water 5 times, filtered to remove impurities, and then soaked with anhydrous ethanol and n-hexane to replace the solvent in the gel, and then soaked with trimethylchlorosilane for 3h to obtain sample 2;

[0058] S3. Sample 2 was dried at 85°C to obtain silica aerogel, and ground in a ball mill for 3 h to obtain powder sample 3;

[0059] S4. The powder sample 3 was added to 100 mL of anhydrous ethanol dissolved with 0.01 g of lanthanum nitrate hexahydrate and 0.01 g of ferric chloride, stirred at 50 ° C for 4 h, and then dried in an oven at 85 ° C for 4 h. After removing the ethanol, it was calcined in a muffle furnace at 700 ° C for 4 h to obtain a silica aerogel adsorbent introduced with iron and lanthanum elements. The silica aerogel was washed with ethanol and dried at 80 ° C to obtain sample 4;

[0060] S5. Dissolve 5 g of cellulose acetate in 45 g of acetone, stir at room temperature for 30 min, add 6 g of sample 4 and 15 g of water, stir evenly, pour the mixture into a mold, remove the solvent to obtain a lanthanum-iron functionalized silica aerogel dephosphorus agent.

[0061] Example 7: A method for preparing a lanthanum iron functionalized silica aerogel dephosphorization agent, comprising the following steps:

[0062] S1. Take 30g of water glass with a solid content of 36%, add 150g of deionized water and stir for 30min to dilute to a solid content of 6%, then prepare 20g of dilute sulfuric acid with a concentration of 20%, and drip 20g of dilute sulfuric acid at a speed of 1500rpm for 3h, and age at room temperature for 24h to obtain gel sample 1;

[0063] S2. Gel sample 1 was crushed, washed with water 5 times, filtered to remove impurities, and then soaked with anhydrous ethanol and n-hexane to replace the solvent in the gel, and then soaked with trimethylchlorosilane for 3h to obtain sample 2;

[0064] S3. Sample 2 was dried at 85°C to obtain silica aerogel, and ground in a ball mill for 2 h to obtain powder sample 3;

[0065] S4. The powder sample 3 was added to 100 mL of anhydrous ethanol dissolved with 0.05 g of lanthanum nitrate hexahydrate and 0.02 g of ferric chloride, stirred at 50 ° C for 4 h, and then dried in an oven at 85 ° C for 4 h. After removing the ethanol, it was calcined in a muffle furnace at 600 ° C for 4 h to obtain a silica aerogel adsorbent introduced with iron and lanthanum elements. The silica aerogel was washed with ethanol and dried at 85 ° C to obtain sample 4;

[0066] S5. Dissolve 3 g of cellulose acetate in 47 g of acetone, stir at room temperature for 30 min, add 5 g of sample 4 and 15 g of water, stir evenly, pour the mixture into a mold, remove the solvent to obtain a lanthanum-iron functionalized silica aerogel dephosphorus agent.

[0067] Comparative Example 1:

[0068] The dephosphorus removal agent used in Example 1 was washed with clean water, dried in an oven at 80°C, placed in a 80g / L NaOH solution, and shaken at 80°C for 24h to desorb phosphorus, which was repeated 3 times. A wastewater dephosphorus adsorption test was conducted.

[0069] Comparative Example 2:

[0070] The dephosphorus removal agent used in Comparative Example 1 was washed with clean water, dried in an oven at 80°C, placed in a 80g / L NaOH solution, and shaken at 80°C for 24h to desorb phosphorus, which was repeated 3 times. A wastewater dephosphorus adsorption test was conducted.

[0071] Performance Testing:

[0072] The phosphorus removal agent in Example 1 was washed with clean water, dried in an oven at 80°C, placed in a 80 g / L NaOH solution, and shaken at 80°C for 24 h to desorb phosphorus. This was repeated three times to conduct a wastewater phosphorus removal adsorption test.

[0073] The water samples used in Examples 1 to 7 were taken from a water purification plant in Zhanjiang City, with a total phosphorus concentration of 1.8 mg / L. 0.1 g of the sample in the example was added to 1 L of phosphorus-containing wastewater, stirred at 200 rpm for 30 min, then allowed to settle for 15 min, the supernatant was extracted to determine the total phosphorus, and the total phosphorus was determined by ultraviolet spectrophotometry. The total phosphorus removal rate was calculated, and the results are shown in Table 1 below:

[0074] Table 1. Phosphorus removal rate of adsorbent prepared in various examples

[0075] project Phosphorus removal rate Example 1 87.21% Comparative Example 1 80.14% Comparative Example 2 73.14% Example 2 85.14% Example 3 84.38% Example 4 83.78% Example 5 83.04% Example 6 81.64%

[0076] Data Analysis:

[0077] Analysis of phosphorus removal rate: Example 1 has the highest phosphorus removal rate, reaching 87.21%. With the changes in the raw material ratio and reaction conditions in each example, the phosphorus removal rate shows certain fluctuations. For example, the phosphorus removal rates of Examples 2-6 are 85.14%, 84.38%, 83.78%, 83.04%, and 81.64%, respectively, showing a gradually decreasing trend, which shows that different preparation conditions have a significant effect on the phosphorus removal effect. Comparative Examples 1 and 2 are tests after desorption of the phosphorus removal agent used in Example 1. The phosphorus removal rates are 80.14% and 73.14%, respectively, which are lower than those of Example 1 used for the first time, indicating that repeated use will reduce the phosphorus removal effect of the phosphorus removal agent, but it can still maintain a certain phosphorus removal capacity.

[0078] Influence of raw material ratio:

[0079] 1. Water glass and dilute sulfuric acid: In each example, the solid content of water glass varies from 6% to 7.2%, the concentration of dilute sulfuric acid varies from 15% to 20%, and the amount and time of addition are also different. For example, in Example 1 and Example 2, the solid content of water glass and the concentration of dilute sulfuric acid are different, which may affect the formation of wet gel and the subsequent structure of aerogel, and thus affect the phosphorus removal rate;

[0080] 2. Lanthanum nitrate hexahydrate and ferric chloride: The mass ratios of lanthanum nitrate hexahydrate and ferric chloride vary greatly in different embodiments, ranging from 5:1 to 1:25. For example, the mass ratios in embodiment 1 are 2:1 and those in embodiment 5 are 1:2. Different mass ratios may change the active sites of phosphorus adsorption by aerogels, thereby affecting the phosphorus removal effect.

[0081] 3. Cellulose acetate and water: The concentration of cellulose acetate solution and the mass ratio of water added to cellulose acetate varied between 1%-30% and 8:1-1:1. This may have affected the molding and physical properties of the final dephosphorus remover, such as flexibility, porosity, etc., and indirectly affected the dephosphorus removal performance.

[0082] Effect of reaction conditions:

[0083] 1. Stirring speed and time: The stirring speed ranges from 1200r / min to 2000r / min, and the time for adding dilute sulfuric acid is mostly 3h. Stirring may affect the uniformity of the reaction. Different speeds will result in different uniformity of the reactants, which in turn affects the quality of the product and the phosphorus removal effect.

[0084] 2. Drying and calcination temperature: The constant temperature drying temperature is 50-90°C, and the calcination temperature is 600-700°C. Temperature has an important influence on the structure and performance of aerogel. Different drying and calcination temperatures may change the pore structure, specific surface area and the existence form of metal elements of aerogel, thereby affecting the phosphorus removal capacity.

[0085] Those skilled in the art should understand that the discussion of any of the above embodiments is merely illustrative and is not intended to imply that the scope of the present invention is limited to these examples. Under the concept of the present invention, the technical features in the above embodiments or different embodiments may be combined, the steps may be implemented in any order, and there are many other variations of the different aspects of the present invention as described above, which are not provided in detail for the sake of simplicity.

[0086] The present invention is intended to cover all such substitutions, modifications and variations that fall within the broad scope of the appended claims. Therefore, any omissions, modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the scope of protection of the present invention.

Claims

1. A method for preparing a lanthanum iron functionalized silica aerogel dephosphorization agent, characterized in that: The following steps are involved: Step S1. Add water glass to deionized water and stir for 30 minutes to dilute, then add dilute sulfuric acid at a speed of 1200-2000 rpm, and then age at room temperature for 12-24 hours after the dripping is completed for 3 hours to obtain gel sample 1; Step S2. Gel sample 1 was crushed, washed with water for 5 times, filtered to remove impurities, and then soaked with anhydrous ethanol and n-hexane to replace the solvent in the gel, and then soaked with trimethylchlorosilane for 3 hours to obtain sample 2; Step S3. Drying sample 2 at a constant temperature of 60-90° C. to obtain silica aerogel, and grinding the aerogel in a ball mill for 2-3 h to obtain powder sample 3; Step S4. dissolving lanthanum nitrate hexahydrate and ferric chloride in anhydrous ethanol and mixing them evenly to obtain a lanthanum-iron composite solution; Step S5. Add the powder sample 3 to the lanthanum-iron composite solution, stir at 50°C for 4 hours to remove ethanol, and then calcine in a muffle furnace at 600-700°C for 4 hours to obtain a silica aerogel adsorbent introduced with iron and lanthanum elements, wash the silica aerogel with ethanol, and dry at 80-85°C to obtain sample 4; Step S6. Dissolve cellulose acetate in acetone, stir for 30 minutes at room temperature, add sample 4 and water, stir evenly, pour the mixture into a mold, remove the solvent, and obtain a lanthanum-iron functionalized silica aerogel dephosphorus agent.

2. The method for preparing the lanthanum-iron functionalized silica aerogel dephosphorization agent according to claim 1, characterized in that: The usage ratio of water glass, deionized water and dilute sulfuric acid in step S1 is 30:120-150:20-30.

3. The method for preparing the lanthanum iron functionalized silica aerogel dephosphorization agent according to claim 1, characterized in that: The solid content of the water glass in step S1 is 36%.

4. The method for preparing the lanthanum-iron functionalized silica aerogel dephosphorization agent according to claim 1, characterized in that: The solid content of the diluted water glass in step S1 is 6%-7.2%.

5. The method for preparing the lanthanum-iron functionalized silica aerogel dephosphorization agent according to claim 1, characterized in that: The concentration of the dilute sulfuric acid in step S1 is 15%-20%.

6. The method for preparing the lanthanum-iron functionalized silica aerogel dephosphorization agent according to claim 1, characterized in that: The usage ratio of sample 1, anhydrous ethanol, n-hexane and trimethylchlorosilane in step S2 is 10 g: 150-200 mL: 100-120 mL: 100-120 mL.

7. The method for preparing the lanthanum-iron functionalized silica aerogel dephosphorization agent according to claim 1, characterized in that: The usage ratio of lanthanum nitrate hexahydrate, ferric chloride and anhydrous ethanol in step S4 is 0.01-0.05 g: 0.01-0.025 g: 100 mL.

8. The method for preparing the lanthanum-iron functionalized silica aerogel dephosphorization agent according to claim 1, characterized in that: The usage ratio of cellulose acetate, acetone, sample 4 and water in step S6 is 3-5:45-47:4-8:10-15.

9. The method for using the lanthanum iron functionalized silica aerogel dephosphorization agent according to any one of claims 1 to 8, characterized in that: The following steps are involved: The prepared lanthanum iron functionalized silica aerogel dephosphorizer is added into phosphorus-containing wastewater, stirred and allowed to settle to remove phosphorus from the phosphorus-containing wastewater.